Integrated policy strategies for resolving separatism in Papua to achieve national security and stability - Wijanarko, Trias (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Separatism in Papua has long posed significant challenges to Indonesia’s national security, social stability, and economic development. This issue arises from a range of factors, including historical grievances, ethnic disparities, economic inequality, and limited access to basic services, which perpetuate discontent among the Papuan population. Despite various governmental efforts, including military measures, special autonomy provisions, and economic development programs, the effectiveness of these approaches remains limited, often failing to address the root causes of the conflict comprehensively. Methods: This study adopts a systematic literature review approach, gathering and analyzing academic articles, government reports, and other relevant sources published within the last decade. Through a thematic analysis, we identify the primary factors contributing to separatism in Papua, assess the current governmental responses, and evaluate their impacts on social, economic, and political stability in the region. Findings: The analysis reveals that the current approaches to addressing separatism in Papua are fragmented and sectoral, often leading to an overlap of roles among security forces and tensions between authorities and civilians. While economic and social policies aim to improve conditions, significant obstacles remain, including challenging geography, limited infrastructure, and budgetary constraints. A holistic strategy that integrates political, economic, security, legal, human rights, and diplomatic perspectives is essential to foster sustainable peace and development in Papua. Conclusion: A comprehensive policy framework that includes effective special autonomy, inclusive economic development, human rights protection, and international diplomacy is crucial to mitigating the separatist threat in Papua. Such a framework requires coordinated roles among local leaders, law enforcement, and the community to create culturally aligned solutions and prevent future conflict. Novelty/Originality of this article: By synthesizing recent literature and identifying gaps in current policies, this research contributes a novel perspective that highlights the importance of balanced, cohesive policy actions for resolving complex socio-political issues.